Electronic Structure of Pt and Pt-Co Nanoparticles with O2 and O2/H2O Adsorption Revealed by In Situ XAFS and Hard X-Ray Photoelectron Spectroscopy. (29th August 2016) - Cui, Yi-Tao; Harada, Yoshihisa; Hatanaka, Tatsuya; Nakamura, Naoki; Ando, Masaki; Yoshida, Toshihiko; Ikenaga, Eiji; Ishii, Kenji; Matsumura, Daiju; Li, Rui; Oshima, Masaharu
Abstract : The electronic structures of Pt and Pt-Co nanoparticles with O2 adsorption and O2 /H2 O co-adsorption were investigated by in situ hard X-ray photoelectron spectroscopy (HAXPES) and in situ high resolution fluorescence detection X-ray absorption spectroscopy (HERFD-XAS) to clarify the effects of water adsorption on fuel cell cathode catalysis surface. The experimental results suggest that under the pressure of 1 mbar, the adsorption of H2 O hinders the successive O2 adsorption on Pt surface, while under the pressure of 1 bar, the adsorption of H2 O enhances the adsorption of O2 on Pt surface. This water effect is found to be more significant on Pt surface than on Pt-Co surface. These results would be helpful to understand how the water affects the fuel cell performance and why Pt-Co nanoparticles show higher oxygen reduce reaction (ORR) activity than Pt nanoparticles.